Rethinking the shadow economy in terms of happiness. Evidence for the European Union Member States - Achim, Monica Violeta; Borlea, Sorin Nicolae; Găban, Lucian Vasile; Cuceu, Ionut Constantin (Technological and Economic Development of Economy, 2018)
This paper’s goal is to highlight how happiness affects the level of shadow economy, by using many control variables within different types of potentially determining factors of shadow economy. Another main contribution consists in the systematic comparison between old and new European Union member states in terms of determinants of shadow economy, including happiness. Our findings consist in the fact that happier people are more likely to act honestly, thus causing a decrease in the size of shadow economy and this result is valid both for old and new European Union countries. In addition, we found that the quality of public governance and the richness of a country are associated with a lower propensity towards shadow economy for all the member states. However, the relationship between public governance and shadow economy are never sig-nificant when the happiness and richness variables vary simultaneously. Our research reveals that the shadow economy in European Union countries is explained in percent of about 62% by richness and happiness of the people. Contrary to our expectations, the fiscal pressure seems not to be a determinant for shadow economy in the European Union space.First published online 4 December 2016